TRANSFORMATION OF KAMASAN PUPPET PAINTING ART IN POSTMODERN ERA - Mudana, I Wayan Mudana; Kumbara, A.A. Ngurah Anom; Rai, I Wayan Rai; Dhana, I Nyoman Dhana (E-Journal of Cultural Studies; Vol 8 No 3 (2015): Volume 8, Number 3, August 2015, 2015)
The Kamasan Puppet Painting Art “Seni Lukis Wayang Kamasan (abbreviated to SLWK)” is a traditional art which grows and develops at Kamasana Village, Klungkung, Bali. Traditionally, it is used as the worshipping media; it is bound to the native puppetry story and is painted collectively and communally. In the modern era SLWK is commercialized by the painters as a profession in order to earn money to support their families. The postmodern era SLWK has been transformed, causing it to change. The data in the present study were taken from in-depth interview, observation, library research, and documentary study. The theory of practice, the theory of commodification, and the theory of postmodern aesthetics were used in the present study. The result of the study shows; first , the things which have caused SLWK to be transformed are (1) economic motivation, (2) self identity, (3) painting creativity, (4) globalization, and (5) tourism. Second , the forms of the transformation of SLWK in the postmodern era are (1) change in production, (2) change in distribution, (3) change in consumption. Third , the implication of the transformation of SLWK in the postmodern era includes (1) the fact that the local traditional values are becoming degraded; (2) improvement in prosperity; (3) the fact that the freedom in painting is becoming shackled; (4) the social consumption and distribution are becoming wider; (5) the fact that female painters have appeared; and (6) the fact that the creative industry is becoming developed.
Keywords: Transformation, Seni Lukis Kamasan (SLWK), and Postmodern.